Characteristics of Entomoparasitic Nematodes of Small Rodent Fleas - G. A. Eroshenko; E. I. Koshel’; A. M. Porshakov; T. V. Knyazeva; Ya. M. Krasnov; T. V. Mokrousova; L. A. Novichkova; L. V. Anisimova (Проблемы особо опасных инфекций, 2016)
Entomoparasitic nematodes are the natural regulators of numbers of fleas – plague vectors in natural plague foci. They have an impact on the intensity of epizootic process, progressing in these foci.Objective of the study is to examine entomoparasitic nematodes from fleas of the souslik and vole, collected in the territory of Povolzhsky Region.Materials and methods. Presented are the results of morphological and genetic analysis of entomoparasitic nematodes, flea parasites – Citellophilus tesquorum, Amphipsylla rossica and Ctenophthalmus secundus, collected from the small ground squirrel Spermophilus pygmaeus and social vole Microtus socialis, respectively.Results and conclusions. Established has been morphological identity of nematode parasitic females isolated from all the three species of fleas, and a high degree of similarity to the previously described Rubzovinema ceratophylla, parasitizing on C. tesquorum fleas. Substantiated has been the belonging of parasitic nematodes isolated from fleas C. tesquorum, А. rossica and C. secundus, to one and the same species, specified as Rubzovinema sp., based on the high percentage of the homology of the nucleotide sequences of rRNA genes (99.3–100 %). This species differs from the previously described monoxenous R. ceratophylla in absence of strict host specificity.